Studi Kelayakan Pengembangan Kawasan Budidaya Air Tawar di Kabupaten Tanjung Jabung Timur - Sugihartono, Muhammad; Harianto, Eko; Ghofur, Muarofah (Universitas Batangahari Jambi, 2025)
Tanjung Jabung Timur Regency still has a relatively low fish production in Jambi Province, especially for freshwater fisheries, so there is still a high potential for increasing production. In order to increase fish production and the community's economy, it is necessary to conduct research related to the feasibility study of developing a freshwater fish farming area in the selected area. This research aims to select sites and assess the feasibility of developing freshwater aquaculture areas in Tanjung Jabung Timur Regency. The research was conducted over 8 months, from April to December 2022. There are three locations for the feasibility study of freshwater aquaculture area development, namely Talang Babat Village, Parit Culum II Village, and Rano Village, Sabak Barat Subdistrict, Tanjung Jabung Timur Regency. These three candidate locations are potential subdistricts in this regency that have generally been used (land use) for freshwater fish farming activities. The research was conducted by comparing the results of the suitability of the research parameters used between one candidate location and another. Several aspects of location suitability were used, including legal aspects, natural resources/technical aspects, artificial resources/infrastructure, socio-cultural aspects, and business/economic aspects. Based on the results of the semi-quantitative analysis, it was found that.